PERAN EPISTIMOLOGI SOSIAL DALAM ADMINISTRASI PENDIDIKAN - Nikmatullaili Nikmatullaili; Nurhizrah Gistituati; Rifma Rifma (Jurnal Dedikasi Pendidikan, 2024)
While there is much epistemological debate in the delivery of education, epistemology and the search for scientific studies on educational administration are somewhat less related to research that has a direct impact on educational practice. As a field of knowledge production, educational administration carries out many analyses related to the issue of scientific progress. Its contribution can be made in conjunction with others. That is, innovation or scientific significance is an act of scientific (social) distinction. This means deliberately getting involved with another. In this paper, education administration knowledge is very limited. However, regardless of the diversity of opinion, this paper can be used as a basis for investigating knowledge about the role of social epistemology in educational administration. The analysis carried out shows that social epistemology can be used to transfer knowledge claims in education